2018
DOI: 10.3390/app8020308
|View full text |Cite
|
Sign up to set email alerts
|

Excitation of Wet Perovskite Films by Ultrasonic Vibration Improves the Device Performance

Abstract: Abstract:In this work, a novel, facile, and low-cost mechanical post treatment technique, i.e., ultrasonic substrate vibration post treatment (SVPT) is applied on wet spun perovskite layers. The effect of varying the time of the SVPT on the characteristics of the perovskite crystals and the perovskite film is studied, in order to achieve the optimum time duration of the SVPT. Among the results, it is found that the application of only three minutes of the SVPT (for the ultrasonic vibration assembly used in thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 50 publications
0
14
0
Order By: Relevance
“…So far, these results have shown that the solvent depletes and the interfacial energy of perovskite films decreases with increasing the time of imposed ultrasonic vibrations. In addition, in previous studies, it has been shown that ultrasonic vibrations result in an improvement in the perovskite light absorption 8 and a decrease 25 or increase 9 in the grain size, depending on the choice of the substrate and solutions, as discussed in the Introduction section. The aforementioned effects may be because of the variations in the nucleation and crystallization of the perovskite, under the presence and varying time of ultrasonic vibrations.…”
Section: Acs Omegamentioning
confidence: 93%
See 1 more Smart Citation
“…So far, these results have shown that the solvent depletes and the interfacial energy of perovskite films decreases with increasing the time of imposed ultrasonic vibrations. In addition, in previous studies, it has been shown that ultrasonic vibrations result in an improvement in the perovskite light absorption 8 and a decrease 25 or increase 9 in the grain size, depending on the choice of the substrate and solutions, as discussed in the Introduction section. The aforementioned effects may be because of the variations in the nucleation and crystallization of the perovskite, under the presence and varying time of ultrasonic vibrations.…”
Section: Acs Omegamentioning
confidence: 93%
“…8 This method has also shown applicability to other solution-processed materials, for example, improvement of physical and chemical properties of graphene−TiO 2 , 20 ZnO, 24 and poly(3,4-ethylenedioxythiophene):polystyrene sulfonate 16 thin films. Ahmadian-Yazdi et al 25 performed ultrasonic vibrations on mesoporous structured PSCs before annealing on single and mixed-halide perovskites, and their results demonstrated substantial film coverage and charge-transfer improvement. In another study, Ahmadian-Yazdi et al 8 eliminated the annealing process for perovskite thin-film processing by employing diethyl ether (DEE) as an antisolvent for n-methyl-2-pyrrolidone (NMP) during spin casting.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the Sm 3+ iondoped CsPbCl 3 PeNC film maintain optical performance similar to that of its corresponding PeNCs and exhibit only a partial decrease of PLQY in the film owing to the aggregation of the particles in the film (Figure S15). 43,44 The normalized EL spectra of the as-prepared PeLED devices based on Sm 3+ ion-doped PeNCs with concentrations of 2.6 mol %, 5.1 mol %, and 10.3 mol % are depicted in Figure 4b. It is found that there is an obvious inhomogeneous broadening in EL versus PL.…”
mentioning
confidence: 99%
“…Moreover, to improve the thin-film deposition characteristics, an emerging fabrication method compatible with the solution processing has been systematically surveyed, which will be employed and further studied in this paper. Ultrasonic vibration is an effective method for thin-film fabrication which has the potential to be employed to deposit relatively large-area and uniform films and coatings ,, if the frequency and amplitude are well chosen. Imposing ultrasonic vibrations results in bulk and local micromotions in the fluid, , a flow that will interact with Marangoni-induced flows, as previously discussed.…”
Section: Introductionmentioning
confidence: 99%